2000
DOI: 10.1094/cchem.2000.77.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Peroxidases in Durum Wheat (Triticum durum)

Abstract: Cereal Chem. 77(1): [11][12][13][14][15][16][17] A biochemical study of the main durum wheat milling fractions (bran, embryo, and semolina) showed that peroxidases (POD) were present in multiple forms in the kernel and appeared to be tissue specific: one form for the embryo, one for the endosperm, one for the subaleuronic layer, and one for the outer layers. Large varietal differences were found regarding both the composition and the POD activity. POD activity, detected by diaminobenzidine, was found mainly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
2
28
1
1
Order By: Relevance
“…The POX activity was found to be abundant in bran. Its presence was also reported in the aleurone layer, scutellum and endosperm (Fraignier et al, 2000). According to our study, the average value of durum wheat bran for the POX activity was about 3.7-fold higher than that of debranned durum wheat flour.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The POX activity was found to be abundant in bran. Its presence was also reported in the aleurone layer, scutellum and endosperm (Fraignier et al, 2000). According to our study, the average value of durum wheat bran for the POX activity was about 3.7-fold higher than that of debranned durum wheat flour.…”
Section: Resultssupporting
confidence: 77%
“…However, no significant difference in the mean POX activity was observed between debranned flour and bran of bread wheat (Table 4). Fraignier et al (2000) demonstrated the presence of multiple isoforms of POX in the durum wheat grain, also with a tissue-specificity, suggesting for each of them a particular function. The bran POX, in the presence of hydrogen peroxide, may act to strengthen cell walls through lignin cross-linking, thus inhibiting fungal penetration and providing the protection of embryo and nutrient-rich endosperm (Jerkovi c et al, 2010).…”
Section: Resultsmentioning
confidence: 88%
“…Carotenoid pigment degradation is also affected by the peroxidases (PERs), a class of enzymes that can oxidise a large number of compounds at the expense of hydrogen peroxide (Fraignier et al 2000). Fortunately, PERs do not show activity during pasta processing, probably because of the lack of availability of hydrogen peroxide (Icard-Vernière and Feillet1999;Feillet et al 2000).…”
Section: Carotenoid Biosynthesis and Degradation Pathways And Their Cmentioning
confidence: 99%
“…Matsuo and Irvine (1967) reported that the inherited brownness was the result of nonenzymatic soluble proteins. Contrarily, Fraignier, Michaux‐Ferrière, and Kobrehel (2000) suggested that enzymatic brownness based on a POD isoform P‐5 was found in greater amount in the endosperm of a cultivar of durum wheat with darker pasta could be responsible for genotypic differences in brownness of pasta. On the other hand, PPO activity levels in wheat have been more associated with the growing environment than genotype (Kiszonas, Fuerst, & Morris, 2013; Park et al., 1997).…”
Section: Introductionmentioning
confidence: 99%